State Intimate Partner Violence-Related Firearm Laws and Intimate Partner Homicide Rates in the United States, 1991 to 2015 - Díez, Carolina; Kurland, Rachel P; Rothman, Emily F; Bair-Merritt, Megan; Fleegler, Eric; Xuan, Ziming; Galea, Sandro; Ross, Craig S; Kalesan, Bindu; Goss, Kristin A; Siegel, Michael (Annals of internal medicine, 2017)
To prevent intimate partner homicide (IPH), some states have adopted laws restricting firearm possession by intimate partner violence (IPV) offenders. "Possession" laws prohibit the possession of firearms by these offenders. "Relinquishment" laws prohibit firearm possession and also explicitly require offenders to surrender their firearms. Few studies have assessed the effect of these policies. To study the association between state IPV-related firearm laws and IPH rates over a 25-year period (1991 to 2015). Panel study. United States, 1991 to 2015. Homicides committed by intimate partners, as identified in the Federal Bureau of Investigation's Uniform Crime Reports, Supplementary Homicide Reports. IPV-related firearm laws (predictor) and annual, state-specific, total, and firearm-related IPH rates (outcome). State laws that prohibit persons subject to IPV-related restraining orders from possessing firearms and also require them to relinquish firearms in their possession were associated with 9.7% lower total IPH rates (95% CI, 3.4% to 15.5% reduction) and 14.0% lower firearm-related IPH rates (CI, 5.1% to 22.0% reduction) than in states without these laws. Laws that did not explicitly require relinquishment of firearms were associated with a non-statistically significant 6.6% reduction in IPH rates. The model did not control for variation in implementation of the laws. Causal interpretation is limited by the observational and ecological nature of the analysis. Our findings suggest that state laws restricting firearm possession by persons deemed to be at risk for perpetrating intimate partner abuse may save lives. Laws requiring at-risk persons to surrender firearms already in their possession were associated with lower IPH rates. Robert Wood Johnson Foundation.